INTENTION TO USE ELECTRONIC FOOD ORDERING AMONG UNIVERSITIES STUDENTS IN KUALA TERENGGANU - Noorazlin Ramli; Nur Aisyah Syafiqah Muhammad Khairi Sham; Nur Farthiha Binti Mohamad; Fatimah Abd Ghani; Wan Nazriah Wan Nawawi (International Journal of Accounting, Finance and Business, 2020)
Electronic or online food ordering is the one of the technology that has beendeveloped to ease the food business. Therefore, the purpose of this paper is to determine thestudents’ intention to use electronic food ordering in Kuala Terengganu. The quantitativemethod was applied through a questionnaire survey. 120 questionnaires were distributed to therespondents that were randomly selected in two universities in Kuala Terengganu namelyUniversiti Sultan Zainal Abidin (UniSZA) and Universiti Teknologi Mara (UiTM). 100questionnaires out of a total of 120 questionnaires were completed and returned with reliableand meaningful results. The result clearly shows that majority of the students were have apositive intention to use electronic food ordering due to perceived convenience, customercontrol, attractive marketing and eagerness to use technology. Besides, they feel that electronicfood ordering is user-friendly and they can get sufficient information to order. Hence, this studyis vital in providing knowledge and information about the significance of electronic foodordering to the food industry player especially to the food operator and manufacturer. In linewith that, it will help community and local people in expanding their business and makeadvantage of electronic food ordering as one of the marketing strategy and reduceunemployment rate thus contribute to a better national income.